2017
DOI: 10.1002/lio2.131
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on patients at high‐risk for obstructive sleep apnea undergoing ear, nose, and throat surgeries

Abstract: BackgroundObstructive sleep apnea (OSA) may be related to episodes of oxygen de‐saturation, hypercapnia, cardiovascular dysfunction, cor‐pulmonale, and pulmonary hypertension. STOP‐BANG is an acronym for eight specific questions used to assess the likelihood of OSA. If the individual exhibits three or more of these indicators, he/she should be considered to be at high risk for OSA complications. Therefore, the decision of proceeding with inpatient versus outpatient ENT surgery still remains controversial. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…This is interesting given that the presence of OSA commonly requires patients to be admitted to the hospital or observed in a monitored setting. Several prior studies have found that patients with OSA undergoing head and neck surgery are not at increased risk for postoperative complications and can be safely managed in an outpatient setting; our study supports these findings 23,24 . Because inpatient surgery has significantly higher costs compared to ambulatory surgery, permitting OSA patients undergoing FESS for CRS to be managed in ambulatory surgical settings with enhanced postoperative monitoring protocols would also reduce hospital expenditures.…”
Section: Discussionsupporting
confidence: 85%
“…This is interesting given that the presence of OSA commonly requires patients to be admitted to the hospital or observed in a monitored setting. Several prior studies have found that patients with OSA undergoing head and neck surgery are not at increased risk for postoperative complications and can be safely managed in an outpatient setting; our study supports these findings 23,24 . Because inpatient surgery has significantly higher costs compared to ambulatory surgery, permitting OSA patients undergoing FESS for CRS to be managed in ambulatory surgical settings with enhanced postoperative monitoring protocols would also reduce hospital expenditures.…”
Section: Discussionsupporting
confidence: 85%